Evaluation of educational programs of pediatrics, orthodontics and restorative departments of babol dental school from the perspective of the students based on the CIPP model - Mitra Tabari; Ziba Nourali; Soraya Khafri; Samane Gharekhani; Iman Jahanian (Babol University of Medical Sciences, 2016)
Introduction: Evaluation is a critical issue to achieve the goals of academic education. The aim of this study was to evaluate the achievement level of educational objectives in Babol dental school using the CIPP (content, input, process, and product) model based on the point of view of students. Materials &Methods: This cross-sectional study was performed using a researcher made questionnaire based on CIPP model for three educational groups of pediatrics, orthodontics and restorative dentistry among dental students accepted in 2008 and 2009. Total scores were calculated for each field and categorized as undesirable, relatively desirable and desirable with scores below 50, 51-70 and 71-100, respectively. Statistical analysis was performed using ANONA, T-test and Tukey HSD tests and p<0.05 was considered significant. Results: The mean scores were desirable in all groups. Mean scores allocated to the content, input, process and product areas were not significantly different in the pediatrics, orthodontics and restorative dentistry groups. Conclusion: Based on the student’s point of view, the pediatrics, orthodontics and restorative dentistry departments of Babol dental school were  successful in achieving educational goals.